Preserving and empowering local languages amidst the Covid-19 pandemic; Lessons from East Kalimantan - Lauder, Allan F.; Lauder, Multamia R.M.T.; Kiftiawati, Kiftiawati (UI Scholars Hub, 2021)
This article brings together two ostensibly separate subjects: language empowerment and the Covid-19 pandemic. It argues that knowledge of local languages can help disseminate health-related information on a regional level. This addresses two problems simultaneously: the problems raised by the intelligibilty of governmental healthcare protocols and the functions of the use of local languages. The article is a case study presenting a number of interventions in the languages of East Kalimantan and can be seen as an inclusive, grassroots example of health communication. The study was initially a modest attempt to generate on-the-ground examples of health information in the dominant languages of the region of East Kalimantan. These studies demonstrate that the local communities of these languages are very enthusiastic about getting involved in the interventions. They also reveal that communication using IT and social media is thriving. One of our observations was that information about this pandemic tends to be understood only by highly educated urban people. This happens because it is conveyed by the government in standard Indonesian, which includes many foreign loanwords. The application of local languages is not just using local language vocabulary, it is instead a trigger to revive the collective memory of disaster management based on local culture. In this case, local languages are recognized and considered useful in helping to break the chain of virus transmission to free Indonesia of the Covid-19 outbreak. There were a number of unexpected developments. We found support for the intervention being rolled out on a national level by Special Task Force for Covid-19 under National Disaster Management Agency (Badan Nasional Penanggulangan Bencana/BNPB). We also welcomed the online publication by the National Agency for Language Development and Cultivation (Badan Bahasa) of the Handbook for managing behavior about health protocols in seventy-seven local languages. The main thrust of this article should therefore be of interest to anyone working to empower local languages and language vitality.